Knitting Fabric with Fractal Geometry: Fractal Theory Applied to Industry 4.0 - Munandar, Taufik; Ihsan Ardiansyah, Muhammad; putra, valentinus galih vidia (Universitas Insan Cendekia Mandiri, 2024)
Knitted fabrics have complex and repetitive patterns, similar to fractal geometry, where fractal theory can be applied in industry 4.0 to optimize the design, production and analysis of complex and efficient textile structures.This study aims to reduce electromagnetic radiation using conductive knit fabrics patterned with fractal geometry and non-conductive knit fabrics with similar patterns. Tests included raw materials (yarn) and fabrics. The yarn was tested using FTIR and SEM, while the fabric was tested for anti-radiation reduction and aesthetics. Conductive yarns of stainless steel polyester filament were interlaced with acrylic yarn using the jacquard technique on a Stoll CMS 540 HP automatic flat knitting machine. The results showed that the conductive knit fabric patterned with fractal geometry was better at absorbing electromagnetic radiation than the non-conductive knit fabric. The radiation test was conducted with sources from smartphones and computer screens at a distance of 10 cm, 20 cm, and 30 cm, while the aesthetic test was conducted using a questionnaire. The novelty of this research lies in the application of fractal geometry motifs, which enhance the protective and aesthetic functions of the fabric, resulting in a functional textile with high visual appeal.